Crystal chemical textures: a record of plumbing system dynamics potentially modulated by ice load - The Pleiades Volcanic Complex, Antarctica. - TOMASSINI, ALICE (Pisa University, 2023)
The Pleiades Volcanic Complex (PVC) is made up of some 20 monogenetic cinder cones, that erupted during the last 900 ka. Their products define a complete moderately alkaline sodic association, representing a uniqueness for both the volcanism in northern Victoria Land (Antarctica) and alkaline volcanic fields made of monogenetic cones. To investigate the origin of such a special signature, FE-SEM textural imaging coupled with EPMA major element analyses of the main mineral phases have been performed. Moreover, clinopyroxene has been selected for LA-ICP-MS trace element analyses and thermobarometry. The observed chemical textures can be complex, but strong zonings of primitive composition are scarce. Each sample of various degrees of evolution is in fact the result of mixing between similar magmas belonging to the same association. Only hawaiites and less evolved mugearites record the mixing with a primitive magma, although not of direct mantle derivation. Thermobarometry, in support of petrographic evidence, suggests the presence of a vertically extended plumbing system, in which fractional crystallisation, coupled with mixing between differently evolved magmas, permits the development of a complete moderately alkaline sodic evolution trend. Such processes need the residence times to be long, in order to have a complete evolution from alkali basalt to trachyte and magma refilling from different ponding levels of the system in shallower reservoirs. The arrival of a mafic, volatile-rich, magma in the shallow reservoirs often precedes the eruptions. Taking into account the geological setting of PVC, the long residence time in the crust could have been provoked by a significant glacio-lithostatic load during glacial stages, which induced a compressive stress on the horizontal plane in the upper crust and inhibited the eruptions. The system was likely episodically fed by newly originated magmas in order to permit the development of a complex, long-lived, plumbing system. Glacial unloading, during major deglaciation or ...